Women in Politics in Osun State, Nigeria: Challenges and Pathways to Inclusive Governance - AKINADE, Ayomiposi Omoniyi; ADELEYE, Mustapha Akande (The Gender Truth Journal, 2026)
This study investigates the factors constraining women’s participation in politics in Osun State, Nigeria, and explores strategies for enhancing their involvement in politics. The study adopted a descriptive survey research design. The population for the study comprised all eligible voters in Osun State, while the sample consisted of 600 respondents. The instrument used for data collection was titled Women’s Participation in Politics in Osun State Questionnaire (WPPOS). The data obtained were analyzed using frequency counts and percentages. The findings revealed that the major barriers to women’s participation in politics in Osun State include violence and thuggery during elections (93%), the cost of vying for political posts (91%), family responsibilities (89%), lack of financial support (87%), unemployment and poverty (83%), and the frequent night meetings of politicians (78%). Suggested pathways to inclusion include financial assistance and support for female aspirants (81%), educating and sensitizing women on the importance of political participation (76%), enactment and enforcement of laws against discriminatory practices (75%), and reduction of illiteracy levels among women (70%). The study concludes that addressing socio-economic and cultural constraints will enhance the political participation of women and promote inclusive governance in Nigeria.